Penetration Testing of a Cyber Safety Family Advice Suite - Stavros, Katsouris (q, 2021)
The purpose of this thesis journal is to perform Penetration Testing techniques in order to test if the “Cyber Safety Advice Suite Parental Console” is vulnerable to any kind of cyber-attack. Moreover, the researcher aims to identify which of the defence mechanisms that support this web application can withstand such attacks, as well as which defence mechanisms will fail. The malicious hacker has as an objective to gain unauthorized access and control of the system without alerting any data or leaving any traits that can backtrack and lead back to the attacker. The purpose of the security and defence methods that are being used by the application’s system, aims to protect it from the intrusion of such attackers. The researcher tests the software to find any threatening vulnerabilities that could compromise or sabotage the system. The process of Penetration Testing and its purpose as well as to why it is necessary, will be discussed in this paper. Additionally, the article mentions the effects and limitations that Penetration Testing had on the “Cyber Safety Advice Suite Parental Console”, as well as the software tools that were used and an explanation of each. Finally, we discuss the results of the research.
Keywords: Penetration Testing; Cyber Safety Family Advice Suite Parental Console